KONTRIBUSI USAHATANI PADI SAWAH TERHADAP PENDAPATAN KELUARGA PETANI DI DESA TALIKURAN KECAMATAN SONDER KABUPATEN MINAHASA (Contribution of Rice Farming to the Income of Farmer Families in Talikuran Village, Sonder District, South Minahasa Regency) - Renaldy Najoan; Theodora Katiandagho; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to analyze the income of farmer families and the contribution of paddy field farming income to the income of farmer families in Talikuran Village, Sonder District, Minahasa Regency. The study was conducted from July to September 2022, using both primary and secondary data and analyzed descriptively.The results show that the income of paddy field farmer families in Talikuran Village is Rp.20,730,886, obtained from several sources of income such as paddy field farming, other income outside of paddy field farming, wife's income, and children's income. The contribution of paddy field farming to the family income is 29.39 percent.